Hungarian Monitoring, 3 June 1990 . [Magyar rádiófigyelő], 1990. június 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev-Bush summit - Referendum in Italy Domestic Affairs: - 70% of the Alliance of Young Democrats (Fidesz) party leadership is replaced - Preparations for the Antall-Gorbachev summit - Pozsgay's lecture in West Berlin - The Hungarian Chamber of Ambulancemen is established - Collecting signatures to support the re-establishment of the Bolyai University Külpolitika: - Gorbacsov-Bush találkozó - Népszavazás Olaszországban Belpolitika: - A Fidesz kongresszusán kicserélődött a pártvezetés 70%-a - Az Antall-Gorbacsov találkozó előkészületei - Pozsgay Nyugat-Berlinben tart előadást - Megalakult a Magyar Mentőtiszti Kamara - Aláírásgyűjtés a Bolyai Egyetem visszaállítására